2013
DOI: 10.1186/1476-511x-12-116
|View full text |Cite
|
Sign up to set email alerts
|

Rs12218 In SAA1 gene was associated with serum lipid levels

Abstract: BackgroundSerum amyloid A (SAA) is a kind of apolipoprotein. Several studies indicated that SAA genetic polymorphism rs12218 was associated with carotid atherosclerosis, peripheral arterial disease, and serum uric acid levels. However, the relation between rs12218 and lipid levels remains unclear. This study assessed the correlation between SAA1 gene rs12218 polymorphism and lipid levels in a Chinese population.MethodsA total of 823 participants were selected from the subjects for health check in Shanghai Huas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Regarding our study, we found that variation in SAA gene (rs12218) was significantly associated with the plasma level of total cholesterol, TG, HDLc and LDLc levels in the osteoporosis patients, these results comes on line with Zheng et al 14 & Xie et al 20 …”
Section: Discussionsupporting
confidence: 89%
“…Regarding our study, we found that variation in SAA gene (rs12218) was significantly associated with the plasma level of total cholesterol, TG, HDLc and LDLc levels in the osteoporosis patients, these results comes on line with Zheng et al 14 & Xie et al 20 …”
Section: Discussionsupporting
confidence: 89%
“…As described previously [ 18 , 20 ], SAA1 encodes one important inflammation factor-SAA.. Recently, Xie et al reported that rs12218 polymorphism in SAA1 gene was associated with IMT [ 17 ], HDL-C [ 18 , 19 ], Ankle-brachial index (ABI) [ 20 ], and plasma uric acid levels [ 18 ] which was related to cardiovascular disease in adults. And Zhang et al reported SAA1 gene polymorphism was associated with cerebral infarction [ 21 ].…”
Section: Resultsmentioning
confidence: 98%
“…And Zhang et al reported SAA1 gene polymorphism was associated with cerebral infarction [ 21 ]. Xu et al also reported SAA1 gene polymorphism was associated with lipid levels [ 19 ]. However, the relationship between SAA gene polymorphism and obesity in Children remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the finding that synonymous codon changes resulting from SAA1 SNPs ( e.g. , rs12218), which does not lead to amino acid substitution, has been associated with several diseases including increased serum uric acid level and increased body weight (Xu et al, 2013). How this type of SNPs affects SAA1 function remains unclear, but it may be related to altered SAA1 expression level.…”
Section: Discussionmentioning
confidence: 99%